Kurdish Handwritten Text Recognition: A DenseNet121-Transformer Architecture with Constrained Synthetic Line Generation - Hamad, Karez A.; Shareef, Shareef M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Based on the available peer-reviewed literature, Kurdish handwritten recognition remains at a nascent stage, with existing models limited to isolated character, digit, and word recognition. The demand for digitizing Kurdish handwritten documents has grown rapidly, particularly in regions undergoing government digitization, such as the Kurdistan Regional Government. The primary obstacle hindering progress beyond isolated characters or words is the absence of text-based handwritten datasets. To address this gap, a comprehensive Kurdish handwritten dataset encompassing paragraph-, line-, and word-level samples is first introduced. A recognition architecture combining DenseNet-121 as the CNN backbone with a Transformer-based encoder-decoder for sequence modeling is then proposed for Kurdish handwritten line recognition, representing one of the earliest reported efforts in this domain. To augment the limited line-level training data, a constrained recipe-based synthetic line generation framework is developed that concatenates real handwritten word images while enforcing text uniqueness, single-writer consistency, and leakage-free data partitioning. Additional training strategies are investigated, including cross-lingual transfer learning from Arabic handwritten data and fixed-content handwritten line integration for improving recognition accuracy. The best configuration achieved a character error rate (CER) of 0.0593 and a word error rate (WER) of 0.3083 without language model integration, further reduced to a CER of 0.0534 and a WER of 0.2746 with an 8-g language model. The source code and trained models are publicly available at: https://huggingface.co/Karez/ KHLR.